To multiply the polynomial (b+8)(3b-6), we will use the distributive property.
First, multiply b by 3b and b by -6:
b * 3b = 3b^2
b * -6 = -6b
Next, multiply 8 by 3b and 8 by -6:
8 * 3b = 24b
8 * -6 = -48
Now, combine like terms:
3b^2 - 6b + 24b - 48
Simplify the equation by combining the like terms:
3b^2 + 18b - 48
Therefore, the simplified form of (b+8)(3b-6) is 3b^2 + 18b - 48.
Multiply the polynomial (b+8)(3b−6) to simplify.(1 point)
Responses
3b2+18b−48
b2+18b−36
3b2+30b−48
b2+30b−48
2 answers
thats wrong